VIRTUAL LAUNCH EVENT - 2020 Global Food Policy Report: Building Inclusive Food Systems - Swinnen, Johan; Vos, Rob; McDermott, John; Zseleczky, Laura (2020)
Johan Swinnen, Rob Vos, John McDermott, and Laura Zseleczky GLOBAL FOOD POLICY REPORT VIRTUAL LAUNCH EVENT - 2020 Global Food Policy Report: Building Inclusive Food Systems APR 7, 2020 - 12:15 PM TO 01:15 PM EDT